2013
DOI: 10.1002/jgra.50320
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of kinetic instabilities in the solar wind

Abstract: [1] An analysis of ion non-thermal properties in the fast solar wind based on Ulysses data is reported. The radial evolution of the main proton moments (density, temperature, and drift velocities) and their empirical correlations with other plasma parameters are investigated in detail and compared with theoretical expectations. The stability of the plasma is studied against different ion kinetic instabilities driven by ion temperature anisotropies and differential velocities, focusing on the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 65 publications
8
95
2
Order By: Relevance
“…However, Shaaban et al (2015Shaaban et al ( , 2016 have recently shown that inhibiting effect induced by the anisotropic electrons is stimulated by increasing β e, . Thus, for an average value β e, = 1 indicated by the observations (Štverák et al 2008), also commonly invoked in similar investigations (Hellinger et al 2006;Matteini et al 2013), the EMIC threshold can increase considerably constraining more observational data, see dashed (green) line. On the other hand, the fit with the observations is considerably improved in the presence of suprathermal electrons, i.e., the instability thresholds enhance with decreasing the power-index κ e confirming the results in Figure 3.…”
Section: Instabilities Thresholds Vs Observationssupporting
confidence: 60%
“…However, Shaaban et al (2015Shaaban et al ( , 2016 have recently shown that inhibiting effect induced by the anisotropic electrons is stimulated by increasing β e, . Thus, for an average value β e, = 1 indicated by the observations (Štverák et al 2008), also commonly invoked in similar investigations (Hellinger et al 2006;Matteini et al 2013), the EMIC threshold can increase considerably constraining more observational data, see dashed (green) line. On the other hand, the fit with the observations is considerably improved in the presence of suprathermal electrons, i.e., the instability thresholds enhance with decreasing the power-index κ e confirming the results in Figure 3.…”
Section: Instabilities Thresholds Vs Observationssupporting
confidence: 60%
“…On the other hand, as discussed below, some important kinetic effects are not included in the present model. Of course, even if the effect of temperature anisotropy on the phase velocity of Alfvén waves is negligible, the various instabilities can be caused by temperature anisotropy (Matteini et al, 2013). In the present study, Alfvén wave packets excite the longitudinal fluctuations (deformation of the VDFs).…”
Section: Ion Kineticsmentioning
confidence: 65%
“…Non-thermal properties are expected to be more enhanced closer to the Sun. Reproduced with permission from Marsch et al (1982b) and Matteini et al (2013), c John Wiley and Sons.…”
Section: In Situ Observations Of the Solar Wind Ionsmentioning
confidence: 99%